Neutral-Eosin Y-Catalyzed Regioselective Hydroacylation of Aryl Alkenes under Visible-Light Irradiation - Liu, Haiwang; Xue, Fei; Wang, Mu; Tang, Xinxin; Wu, Jie (Synlett, 2020)
Styrene derivatives were hydroacylated with exclusive anti-Markovnikov selectivity by using neutral eosin Y as a direct hydrogen-atom-transfer (HAT) catalyst under visible-light irradiation. Aldehydes and styrenes with various substituents were tolerated (>20 examples), giving the corresponding products in moderate to high yields. The key acyl radical intermediate was generated from a direct HAT process induced by photoexcited eosin Y. Subsequent addition to styrenes and a reverse HAT process generated the ketone products.
Keywords: hydroacylation; ketones; eosin Y; hydrogen atom transfer; acyl radicals; photocatalysis